The individual watching of one's own video and its influence on future biology teachers´ professional vision - Linda Němečková; Lenka Pavlasová (Universidad de Deusto, 2019)
The student teacher usually learns their trade under the guidance of a mentor during teaching practice. Reflections usually take place after the mentor's observation of the student´s lesson, and take the form of an interview between the two participants. Recently, video recordings have been used advantageously to add an extra dimension to such professional development. In the classroom, at the time of the lesson, future teachers may not notice certain events, but using video helps them review, and analyse their attributes, thereby making the reflective process more effective. The development of 'professional vision' consists of two processes: (1) noticing different events and (2) assessing and appraising themselves.1 This study analysed four written reflections (two pairs from each) from future biology teachers (n = 65) during their practice at ISCED 2 (International Standard Classification of Education 2 - lower secondary education, pupils from 11 to 15 years old) and at ISCED 3 (International Standard Classification of Education 3 - upper secondary education, pupils from 15 to 19 years old) schools. The first reflection in the pair ('pre-reflection') was written without video recordings, and the second ('post-reflection') with the support of video recordings. The reflections were divided into statements, and coded according to Sherin and van Es' categorisation system. Statistically significant changes were found in several categories of professional vision in the students´ statements. During practice at ISCED 2 school (the first practice in the curriculum) students commented more often in the Self, Pedagogy, Management, Evaluate and Alteration categories in postreflection, and less in the Student, Curriculum, Subject, Climate and Describe categories. During (the second) practice at ISCED 3 school, students dealt more with Self and Alteration categories in post-reflection. These findings persuaded us that the use of two practices based on video-supported reflection of one's own lessons is effective in prospective biology teachers' development of their professional vision. Received: 28 May 2019 Accepted: 08 November 2019 Published online: 29 November 2019